Peningkatan Motivasi Siswa Dalam Pembelajaran Sejarah Melalui Pendekatan Kontekstual Sejarah Lokal - Febri Orza (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2019)
This research attempts to solve the problem of the low motivation of students in history learning through contextual local history. This research was conducted in two cycles in four meetings using material at the proclamation of independence on August 17, 1945 which had been carried out in Salimpaung Public High School class XII IPS 2 which used the education unit level curriculum. The results of the study prove that student motivation increased after using local contextual history of 37.50% in fisrt cycle to 58.33% in cycle 2. Student creativity increased from 20.83% in cycle 1 to 45.83% in cycle 2 while assignments increased from 50% in cycle 1 to83.34% in cycle 2. This agreement was used by history teachers in the learning process.